INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND JOB PROMOTION ON EMPLOYEE PERFORMANCE - Hidayati, Ulfa; Irawan, Irawan; Rambe, Muhammad Taher (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This study examines the influence of Organizational Citizenship Behavior and Job Promotion on the Performance of BRI Maros Branch Office employees. This study uses Quantitative Descriptive, with 39 respondents. The data analysis method uses Multiple Linear Analysis. The results indicate that OCB has a positive and significant effect on employee performance, Job Promotion does not have a significant effect on employee performance, and then OCB and Job Promotion simultaneously have a positive and significant effect on the performance of BRI Maros Branch Office employees. The effect of promotion on performance is highly dependent on various factors, including how the promotion itself is performed, expectations related to the promotion, and the characteristics of the individual being promoted. BRI Maros Branch Office employees are a model of employees who always seek satisfaction in their work without being too focused on external rewards. Improving performance is not just about promotion or external recognition. Working well consistently can bring long-term benefits in a career and make employees into better professionals.